Attitudes, knowledge and beliefs about dementia: focus group discussions with Pakistani adults in Karachi and Lahore. Issue 12 (18th December 2020) - Farina, Nicolas; Zaidi, Asghar; Willis, Rosalind; Balouch, Sara
Abstract: Pakistan is a lower middle-income country, which to date has had very little research and policy making to address the challenge of dementia. This study aims to explore the perceptions of dementia in a group of Pakistani adults. A series of focus group discussions were completed during 2017 with men and women in two metropolitan centres in Pakistan (Lahore and Karachi) (N = 40). Two vignettes, depicting someone with mild dementia and someone with severe dementia, were used to facilitate discussions. An induction-led thematic analysis was completed. Five themes were identified, reflecting (a) dementia awareness, (b) responsibility, (c) barriers to health care, (d) identified support needs, and (e) religion. Most participants had little awareness and knowledge about dementia, commonly understood to be a disease of forgetting or just normal ageing. Thus, there is an urgent need of a nation-wide campaign to raise dementia awareness in Pakistan, though this needs to be accompanied by improved, accessible health and social care services.